2002
DOI: 10.1007/s00424-002-0992-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between mechanical power, O2 consumption, O2 deficit and high-energy phosphates during calf exercise in humans

Abstract: Whole-body O(2) uptake ( VO(2)), O(2) deficit and the concentration of high-energy phosphates (determined by (31)P spectroscopy) in human calf muscle were measured during moderate aerobic square-wave exercise of increasing intensity in ten volunteers. Net VO(2) (above resting) increased linearly with mechanical power, yielding a delta efficiency of 13.1%. "Gross" O(2) deficit increased linearly with net VO(2). The fraction of phosphocreatine (PC) split at steady state increased linearly with the mechanical pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…The work rate is given between the vertical lines. Statistically significant effects were marked with * (P <0.001) 31 P-MRS studies reported intramuscular mean pH values between 7.0 and 7.1 (Barstow et al 1994a(Barstow et al , 1994bFrancescato et al 2003;Marsh et al 1991;Rossiter et al 2001Rossiter et al , 2002. Collectively, the intramuscular pH of our volunteers at rest ranged between 6.94 and 7.02.…”
Section: Discussionmentioning
confidence: 79%
“…The work rate is given between the vertical lines. Statistically significant effects were marked with * (P <0.001) 31 P-MRS studies reported intramuscular mean pH values between 7.0 and 7.1 (Barstow et al 1994a(Barstow et al , 1994bFrancescato et al 2003;Marsh et al 1991;Rossiter et al 2001Rossiter et al , 2002. Collectively, the intramuscular pH of our volunteers at rest ranged between 6.94 and 7.02.…”
Section: Discussionmentioning
confidence: 79%
“…Given the complexity of the operation of muscle tissue and the dynamically regulated interplay of local versus global controls of blood perfusion in response to the tissue demand for oxygen, mechanical effects, and aggregation of feedback metabolites, it is no wonder that muscle physiology and diseases thereof remain a highly active field of study. 5,[10][11][12][13][14][15][16][17] Our particular interest is the mechanism of local muscle action and the specific pathology of peripheral arterial disease (PAD). PAD is emphasized in muscle research because it is associated with a rather high morbidity and has a distinctly detrimental effect on the patient's health and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Let us assume that the maximal blood lactate concentration in an élite athlete can attain 20·mmol·l -1 . Thus, since the accumulation of 1·mmol·l -1 lactate in blood is energetically equivalent to the consumption of 3·ml·O 2 ·kg -1 (see di Prampero and Ferretti, 1999), the maximal amount of energy that can obtained from lactate is about: Francescato et al, 2003). We can assume that the muscle mass involved in the all-out effort in question, for an élite sprinter, is about 25% of his body mass (e.g.…”
Section: Energy Balance Of Sprint Runningmentioning
confidence: 99%